2009
DOI: 10.1098/rspb.2009.1142
|View full text |Cite
|
Sign up to set email alerts
|

Does coevolution promote species richness in parasitic cuckoos?

Abstract: Why some lineages have diversified into larger numbers of species than others is a fundamental but still relatively poorly understood aspect of the evolutionary process. Coevolution has been recognized as a potentially important engine of speciation, but has rarely been tested in a comparative framework. We use a comparative approach based on a complete phylogeny of all living cuckoos to test whether parasite–host coevolution is associated with patterns of cuckoo species richness. There are no clear difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 41 publications
1
62
1
1
Order By: Relevance
“…This could explain why Horsfield's bronzecuckoos are monotypic, whereas shining bronze-cuckoos comprise four subspecies and there are 10 or more subspecies of little bronze-cuckoo [42]. Furthermore, if cuckoo chick rejection by hosts proves to be more common than is currently thought, it might also explain the recent evidence that species richness is higher in parasitic cuckoos than non-parasitic cuckoos [55].…”
Section: Resultsmentioning
confidence: 99%
“…This could explain why Horsfield's bronzecuckoos are monotypic, whereas shining bronze-cuckoos comprise four subspecies and there are 10 or more subspecies of little bronze-cuckoo [42]. Furthermore, if cuckoo chick rejection by hosts proves to be more common than is currently thought, it might also explain the recent evidence that species richness is higher in parasitic cuckoos than non-parasitic cuckoos [55].…”
Section: Resultsmentioning
confidence: 99%
“…In theory, coevolution of brood parasites and hosts should lead to increased rates of diversification and increased phenotypic diversity [2,19]. We used two recently developed methods and phylogenies to test these hypotheses explicitly.…”
Section: Discussionmentioning
confidence: 99%
“…For example, brood parasitic Vidua finches, Vidua spp., underwent sympatric speciation as they annexed novel host species [15]. Moreover, specialization on particular host species has led to genetic divergence within some cuckoo and honeyguide species into distinct host-specific races [16][17][18], and Krü ger et al [19] demonstrated that species of parasitic cuckoos had more subspecies than species of non-parasitic cuckoos. Since the appearance of these studies, novel phylogenies [20] and phylogenetic methods [3,21] have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Burung yang berasal dari familia Cuculidae dikenal sebagai burung yang bersifat parasit (Kruger et al, 2009;Ducatez, 2014). Penurunan jumlah individu dan jumlah spesies burung dari familia Cuculidae di areal karst yang mengalami gangguan, dapat mengindikasikan adanya penurunan spesies burung yang menjadi inang burung ini di areal yang mengalami gangguan.…”
Section: Respons Burung Yang Hidup DI Karst Tn Babul Terhadap Perubahunclassified